BioXmark® liquid fiducials to enable radiotherapy tumor boosting in rectal cancer, a feasibility trial. (January 2023) - Opbroek, Thirza J.S.; Willems, Yves C.P.; Verhaegen, Frank; de Ridder, Rogier; Hoge, Chantal; Melenhorst, Jarno; Bakers, Frans; Grabsch, Heike I.; Buijsen, Jeroen; Van Limbergen, Evert J.; Canters, Richard A.M.; Berbée, Maaike
Highlights: BioXmark® is a novel liquid fiducial marker for image-guided radiotherapy. The marker remained stable during chemoradiotherapy in 96% of rectal cancer cases. The fiducial allows for image tracking on CT-based imaging modalities. Marker visibility was good using CT-based imaging without any relevant artifacts. The marker is easy to inject without marker related adverse events. Abstract: Background and purpose: Dose-escalation in rectal cancer (RCa) may result in an increased complete response rate and thereby enable omission of surgery and organ preservation. In order to implement dose-escalation, it is crucial to develop a technique that allows for accurate image-guided radiotherapy. The aim of the current study was to determine the performance of a novel liquid fiducial marker (BioXmark®) in RCa patients during the radiotherapy course by assessing its positional stability on daily cone-beam CT (CBCT), technical feasibility, visibility on different imaging modalities and safety. Materials and methods: Prospective, non-randomized, single-arm feasibility trial with inclusion of twenty patients referred for neoadjuvant chemoradiotherapy for locally advanced RCa. Primary study endpoint was positional stability on CBCT. Furthermore, technical aspects, safety and clinical performance of the marker, such as visibility on different imaging modalities, were evaluated. Results: Seventy-four markers from twenty patients were available for analysis. The marker was stable in 96% of the cases. One marker showed clinically relevant migration, one marker was lost before start of treatment and one marker was lost during treatment. Marker visibility was good on computed tomography (CT) and CBCT, and moderate on electronic portal imaging ( EPI ). Marker visibility on magnetic resonance imaging (MRI) was poor during response evaluation. Conclusion: The novel liquid fiducial marker demonstrated positional stability. We provide evidence of the feasibility of the novel fiducial marker for image-guided radiotherapy on daily cone beam CT for RCa patients.